In-situ functionalization of tetrahedral amorphous carbon by filtered cathodic arc deposition - Sami Sainio (AIP Advances, 2019)
Modification of the surface chemistry of carbon-based nanomaterials is often necessary in order to embrace their full potential. A wide variety of different post-fabrication treatments, such as acid, oxidizing plasma and heat treatments have been described in the literature. However, their specific effects on the materials surface chemistry is typically only vaguely disclosed. Here we report an in-situ method to functionalize tetrahedral amorphous carbon (ta-C) thin films by introducing high purity oxygen into the vacuum chamber during the film fabrication. Additionally, we analyze and compare the material properties of the resulting thin films to those of nitric acid and oxygen plasma treated as well as those with no treatment at all. Using x-ray absorption spectroscopy (XAS), we show that in-situ functionalizing decreases the sp2 content of the surface and increases the amount of carboxyl-like functionalities. Subsequent oxygen plasma treatment further decreases the sp2 fraction and ketone/aldehyde content as well as increases the amount of carboxyl groups. The same trends are observed with the reference ta-C exposed to oxygen plasma treatment. For both materials, a concentrated nitric acid treatment has only a subtle effect on the surface chemistry. Capitalizing on this knowledge, we can selectively produce materials with higher surface loading of specific functional groups, paving the way for application specific material fabrication.